Drum - "Cowley, Joy" "Grimwood, Tracie" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Drum is a people dog, and his favourite people are children. "A true gentleman dog," says Mum. But while everyone in town knows and loves Drum, the old dog doesn't belong to anyone. When Drum has an accident one day, people are happy to take care of him. Will his life be changed by this event?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Dogs Juvenile fiction